Entrepreneurs resilience in the forestry industrial sector of the Province of Misiones – Argentine Republic - Tañski, Nilda Catalina (2021)
Fil: Tañski, Nilda Catalina. Universidad Nacional de Misiones. Facultad de Ciencias Económicas; Argentina.